2007
DOI: 10.1177/0743558407306713
|View full text |Cite
|
Sign up to set email alerts
|

Do I Really Need Someone in Order to Become an Adult? Romantic Relationships During Emerging Adulthood in Italy

Abstract: Italian emerging adults stay at home with their parents until they marry. Being involved in a romantic relationship may be considered one precursor of the success of the transition to adulthood. In this study, 92 dating and 84 nondating emerging adults were compared on when they left the parental home and their future plans. They were also compared on individual outcomes (depression, sense of coherence, and self-esteem) and their perception of parental emotional support. Finally, the influence of parental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 31 publications
(28 reference statements)
7
91
0
5
Order By: Relevance
“…In this period, it is not easy to individuate a key relational reference point. For most emerging adults, the most important person within the social network is represented by the romantic partner (Fincham and Cui 2010;Lanz and Tagliabue 2007). For those not involved in a romantic relationship, family members, in particular parents, represent a reference point.…”
Section: Aims Of the Present Studiesmentioning
confidence: 99%
“…In this period, it is not easy to individuate a key relational reference point. For most emerging adults, the most important person within the social network is represented by the romantic partner (Fincham and Cui 2010;Lanz and Tagliabue 2007). For those not involved in a romantic relationship, family members, in particular parents, represent a reference point.…”
Section: Aims Of the Present Studiesmentioning
confidence: 99%
“…Emerging adults with a good relationship with their parents would be more likely to experience a sense of well-being in the parental home and thus may be attracted to continued co-residence (Lanz & Tagliabue, 2007).…”
Section: Emerging Adulthood and Delayed Home Leavingmentioning
confidence: 99%
“…Researches in Finland and Poland (Trempala & Malmberg, 1998), North America (Arnett, 2003), Israel (Mayseless & Scharf, 2003), Argentina (Facio, Resett, Micocci, & Mistrorigo, 2007), Austria (Sirsch, Dreher, Mayr & Willinger, 2009) and Greece (Petrogiannis, 2011) showed that culture and nationality have a distinct effect on emerging adults' view on adulthood. Other researches have also highlighted how the perception one has of him/ herself as still a youth and/or already an adult is related to age, gender, marital status and the level of education received (Buhl, 2007;Fadjukoff, Kokko & Pulkinnen, 2007;Fierro & Hernández, 2007;Lanz & Tagliabue, 2007;Macek, Bejcek & Vanýckova, 2007). Anyhow, the transition to adulthood remains a conventional construct and one of the key issues is whether and which conditions or events signify the adult status.…”
mentioning
confidence: 99%